AHLI WARIS PENERIMA RADD MENURUT KOMPILASI HUKUM ISLAM PASAL 193 DAN RELEVANSINYA DENGAN SOSIAL KEMASYARAKATAN - Lia Murlisa (Islam Futura, 2015)
Radd is the problem of the heritage distribution which affect the rest of property after the heirs dhawil furud acquire his or her rights sharing. This study aims at knowing the theorem by both scholars and clerics whether reject or receive radd, to understand the completion radd according to the Islamic scholar council and the Compilation of Islamic Law (KHI), as well as to understand the radd concept which is supposed to be practiced in Indonesia. To obtain the answer of the study, the researcher combines empirical and normative law approaches in radd determination and heirs receiver. The research is qualitative which stressing its analysis on the combination of the summarizing process between the Islamic scholar council and KHI, and analyze the relationship dynamics phenomena in the society. The source of the data is collected through library research. The method used in the data analysis is descriptive by describing the concept of radd. The result of the study shows that the Islamic scholars who rejet radd are those who use the argument based on the verse of the Qur'an surah an-Nisa: 13-14, while the Islamic scholars who receive radd based on the verse of the Qur'an surah al-Anfal: 75. The completion of radd according to the Islamic scholars council is to give to all dhawil furud except husband and wife, while KHI give the rest of the property to heirs without any exception. The radd concept which is supposed to be applied in Indonesia is by considering a kinship system in a family as in within is the responsibility transition that must be carried out after the death of heirs, without neglecting the opinion of the Islamic scholars in decision making.